Investigating mobile learning readiness among undergraduates students at Faculty of Education in Universiti Teknologi MARA (UiTM) Shah Alam / Megat Ridwan Megat Adnan - Megat Adnan, Megat Ridwan (2016)
Mobile learning becomes a new learning environment in line with the emergence of mobile and wireless technology. Mobile learning is supported by various technologies such as via voice communication, learning portal on the web, through short message service (SMS) and also social media. Mobile technology are now more established, ubiquitous and interconnected until it expended to more sophisticated trend and lifestyles where it capable to provide social interactions under it internet connectivity. There are some problems in current learning environment that is too rigid to net generation student in the 21st century that only focused for teacher-centred learning and limit students' potential to be flexible, creative and innovative in learning processes. Apart from that, mobile learning is still under research project by educators and researchers to identify the significance of mobile learning could benefit to the education system in Malaysia. Mobile learning is still in embryonic stage in Malaysia because the studies on it are still in the circle of establishing idea, theory, design, types of learning and activities using mobile technologies. This study attempts to investigate the mobile learning readiness among undergraduate students in Universiti Teknologi MARA and to propose recommendation to improve students' readiness on mobile learning. This study employed quantitative and qualitative research approach. A survey questionnaire was conducted involving 302 undergraduate students at Faculty of Education in Universiti Teknologi MARA Shah Alam. The finding of this study informed that students are ready to adopt mobile learning as their new technology usage in learning. Majority of the students owned mobile devices such as smartphones and laptop and it is being used for learning. A test of independent using Mann-Whitney U Test was conducted by adopting Technology Readiness Index 2.0 to test the significant different between the technology readiness index dimensions towards students' group of experience using mobile devices and students' group of semester year. The test was found that the innovation dimension in technology readiness index is the most significant different towards the group of students' experience using mobile devices and students' semester year. This lead to the students' perceives to use new technology in their learning. The result also recommend to improve students' readiness on mobile learning by issued the playing roles of university encouragement, technology usage, playfulness and social influence and pedagogical support.